Use of cryosurgery for treatment of feline squamous cell carcinoma: case report - SILVA, CATARINA RAFAELA; Chaves, Laide Danielle Coelho da Silva Chaves; silva, francisco lima silva; Canuto de Sousa, JACQUELINE MARIA; de Alencar Oliveira, Joyce Rayane; dos Santos Silva, Lucilene; Pinheiro Santos, Laíz; Rebelo Fontenele, Andrea (Pubvet, 2020)
Squamous cell carcinoma is a frequent cutaneous neoplasm in felines, especially those with white coat. The diagnosis is made from the clinical evaluation of the animal and cytological, histopathological or biopsy for confirmation. The present case report is a feline patient with white coat affected by this neoplasm, submitted to laboratory tests, with Cryosurgery being the treatment of choice due to the location of the lesions, performed in a private veterinary clinic in the city of Teresina, Piauí. The treatment was performed under a protocol of 4 sessions biweekly, having efficacy. In view of the results obtained in the therapy used in the feline, it was concluded that among several treatments to be followed under the squamous cell Carcinoma, Cryosurgery is a very effective method of choice.
Keywords: carcinoma; cryosurgery; tumor